Nana in the City - Castillo, Lauren (Boston, 2014)
A young boy is frightened by how busy and noisy the city is when he goes there to visit his Nana, but she makes him a fancy red cape that keeps him from being scared as she shows him how wonderful a place it is
Keywords: City and town life -- Juvenile fiction; Grandmothers -- Juvenile fiction; Courage -- Juvenile fiction; Fiction; Juvenile works